MOTIVASI SOSIAL DAN INSENTIF NON-MATERIAL SEBAGAI FAKTOR PENDORONG KINERJA KARYAWAN DI FOURTEEN ROSES BOUTIQUE HOTEL - I Nyoman Widya Saputra; Kadek Devi Kalfika Anggria Wardani (Berajah Journal, 2026)
This study is motivated by the importance of improving employee performance in the hospitality industry, which highly depends on psychological and non-financial factors. This study aims to determine the effect of Social Motivation and Non-Material Incentives on Employee Performance at Fourteen Roses Boutique Hotel. The research method used is quantitative with a sample of 59 hotel employees. Data were collected through questionnaires using a Likert scale and analyzed using validity test, reliability test, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination using SPSS version 25. The results show that Social Motivation has a positive and significant effect on Employee Performance with a significance value of 0.006 < 0.05. Non-Material Incentives also have a positive and significant effect on Employee Performance with a significance value of 0.000 < 0.05. Simultaneously, Social Motivation and Non-Material Incentives significantly affect Employee Performance with an F value of 128.066 and a significance value of 0.000 < 0.05, contributing 81.4% to employee performance. The conclusion of this study is that improving employee performance can be achieved by strengthening social motivation and providing appropriate non-material incentives in the workplace.